Criminal Liability for Illegal Crypto Asset Investments in Indonesia - Anak Agung Gede Krisnantara Putra (Journal Equity of Law and Governance, 2025)
The development of digital technology has driven the growth of crypto-asset-based investments in Indonesia, but it has also opened up opportunities for illegal investments that risk consumer harm and disrupt economic stability. This study aims to analyze the criminal liability of perpetrators of illegal crypto-asset investments and its impact on consumer protection and national economic security. Using a normative juridical method with a statutory and conceptual approach, this study examines regulations such as the Criminal Code, the Electronic Information and Transactions Law (UU ITE), the Consumer Protection and Protection Law (UU P2SK), as well as regulations from the Commodity Futures Trading Regulatory Agency (Bappebti) and the Financial Services Authority (OJK). The results of the study indicate that legal protection for crypto-asset consumers remains weak, particularly in the case of illegal tokens such as ASIXV2 and EDCCash, which are traded without official authorization. Ineffective law enforcement is influenced by weak inter-agency coordination, a lack of technical competence among officials, and the absence of specific laws comprehensively regulating digital assets. Criminal liability theories such as strict liability and vicarious liability are relevant for application to individual and corporate perpetrators of crime. Furthermore, regulatory ambiguity and light sanctions reduce the deterrent effect and encourage violations. This study recommends the establishment of a Digital Asset Law, strengthening inter-institutional coordination, and enhancing digital literacy and oversight to ensure legal certainty and protect the public from the risks of illegal crypto investments.